1996
DOI: 10.1111/j.1745-9125.1996.tb01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Specification Problems, Police Levels, and Crime Rates*

Abstract: Research on the relationship between police and crime, like many criminological topics, is subject to uncertain causal direction and omitted controls. We recommend procedures that mitigate these problems: the Granger causality test, proxies for missing variables, robustness checks, and making data available to other researchers. Because specification problems are common in the social sciences, this strategy has applicability beyond the issue of police and crime. We analyze yearly police data and UCR crime rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(228 citation statements)
references
References 61 publications
11
208
0
7
Order By: Relevance
“…A significant inverse relation found that more police reduces crime (Marvell and Moody, 1996;Levitt 1996). There is some inconsistency in linking economic variables with all crime.…”
Section: The Effects Of Socio-economic and Demographic Factors On Crimementioning
confidence: 99%
See 1 more Smart Citation
“…A significant inverse relation found that more police reduces crime (Marvell and Moody, 1996;Levitt 1996). There is some inconsistency in linking economic variables with all crime.…”
Section: The Effects Of Socio-economic and Demographic Factors On Crimementioning
confidence: 99%
“…They find that each of the categories of crime they tested are cointegrated with a host of demographic and socioeconomic variables and that dwelling commencements (a proxy for wealth) and urbanization are the most important determinants of crime. Marvell and Moody (1996) analyze yearly police data and crime rates, at the 49 states and 56 cities in separate regressions, pooled over two decades. They find Granger causation in both directions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 Moreover, surveys of empirical research on police and crime in economics (e.g. Cameron, 1988;Marvell and Moody, 1996;Eck and Maguire, 2000) report that the majority of studies fail to find any relationship, with some studies even finding a positive association between the two. This is because most of the existing work faces difficulties in attempting to unravel the direction of causation in the relationship between police resources and crime.…”
Section: Introductionmentioning
confidence: 99%
“…A second noteworthy contribution to the modern police manpower literature is that of Marvell and Moody (1996), who leverage the concept of Granger causality to explore the extent to which police manpower is, in fact, responsive to changes in crime. The motivation behind such an approach is that if crime is responsive to lagged police but police staffing is not responsive to lagged crime, then the case for instrumental variables is weakened considerably.…”
mentioning
confidence: 99%